Priority conservation area of Larix gmelinii under climate change: application of an ensemble modeling - Gao, Minglong; Zhao, Guanghua; Zhang, Shuning; Wang, Zirui; Wen, Xuanye; Liu, Lei; Zhang, Chen; Tie, Niu; Sa, Rula (Frontiers in Plant Science, 2023)
Larix gmelinii (Rupr.) Kuzen is a major tree species with high economic and ecological value in the Greater Khingan Mountains coniferous forest of Northeast China. Reconstructing the priority Conservation Area of Larix gmelinii under Climate could provide a scientific basis for its germplasm conservation and management. The present study used ensemble and Marxan model simulations to predict species distribution areas and delineate priority conservation areas for Larix gmelinii in relation to productivity characteristics, understory plant diversity characteristics, and climate change impacts. The study revealed that the Greater Khingan Mountains and the Xiaoxing'an Mountains, with an area of approximately 300 974.2 km2, were the most suitable for L. gmelinii. The stand productivity of L. gmelinii in the most suitable area was significantly higher than that in the less suitable and marginally suitable areas, but understory plant diversity was not dominant. The increase in temperature under future climate change scenarios will reduce the potential distribution and area under L. gmelinii; the species will migrate to higher latitudes of the Greater Khingan Mountains, while the degree of niche migration will gradually increase. Under the 2090s-SSP585 climate scenario, the most suitable area for L. gmelinii will completely disappear, and the climate model niche will be completely separated. Therefore, the protected area of L. gmelinii was demarcated with a target of the productivity characteristics, understory plant diversity characteristics and climate change sensitive area, and the current key protected area was 8.38 × 104 km2. Overall, the study’s findings will lay a foundation for the protection and rational development and utilization of cold temperate coniferous forests dominated by L. gmelinii in the northern forested region of the Greater Khingan Mountains.